FEASIBILITY TEKNIS PEMBANGUNAN KANDANG AYAM CLOSED HOUSE BPU - RENI SULITYAWATI; YOHANES WAHYU DWI YUDONO (Fakultas Teknik, Universitas Wijayakusuma Purwokerto, 2021)
ABSTRACT BPU closed house system cages are closed cages that ensure the safety of livestock in contact with other organisms, with good ventilation arrangements available air and a conducive climate for livestock so as to minimize stress levels. In order to support the planning for the construction of the chicken coop, a geological engineering investigation is needed. Technical Feasibility of Closed House Chicken Coop Development at BPU Jenderal Soedirman University aims to identify soil and rock types, analyze soil strength, potential for soil movement, analyze soil physical and mechanical properties as a result of sondir testing, engineering geological drilling at the location of the development plan as well as recommendations for the right type of foundation. The results of the investigation obtained that the geomorphology of the planned location was included in the Denudational Ridge/Sloping Hills unit, the slope angle was 8-13%, the height difference was 20 meters. Rock types consist of claystone and sandstone as inserts, interludes. Soil strength is included in the very stiff-stiff category (UCS Classification), but still has a fairly good bearing capacity, there is a lot of hard and dry soil. Hard soil layers from the results of the six CPT test points (sondir) were found to vary at a depth of 5.40-9.60 meters. The results of the N-SPT test at two engineering geological drilling points show the depth of the hard soil layer at intervals of 5-6 meters. The results of laboratory tests on the physical and mechanical properties of the soil at a depth of 3 meters resulted in the shear angle numbers: 26.05o (point B1) and 26.79o (point B2); cohesion: 0.2499 kg/cm2 (point B1) and 0.2387 kg/cm2 (point B2), the type of soil that can be interpreted is sandy soil with dense conditions. Recommended depth of foundation to be adapted to the design and analysis of building capacity. The depth of the foundation is 5-6 meters, the result of N-SPT >30 can be constructed with a maximum bearing capacity of 20 tf/m2. The recommended types of foundations that can be proposed are river stone foundations and foot plate foundations. Key words : Technical Feasibility, geomorphology, engineering geology,